Families Benefiting from Social Assistance in Poland - Strategies and Barriers to Poverty Reduction - Pokrzywa, Magdalena (European Journal of Sustainable Development, 2020)
The article aims to characterize the remedial strategies undertaken by Polish families using social assistance to minimize material deprivation and the main barriers to empowerment of such families. The source of data are the results obtained as part of the author’s own research, which were conducted with social workers in Poland and had quantitative (500 CATI) and qualitative (90 IDI) nature. In families living in difficult economic conditions, both active and passive activities are used to obtain the missing funds. Active strategies include taking up a job (permanent, additional or occasional, legal or in the so-called ‘gray area’), selling or exchanging skills, time and goods, borrowing money, or applying for support to institutions (which is mainly a female domain). Women also implement many passive strategies that involve saving or reducing consumption by, for example, preparing dishes from cheap products, shopping in places with the lowest prices, buying second-hand items, etc. The main barriers to minimizing the poverty of families benefiting from social assistance in Poland are related to their life attitude and the gender of its members. Remedial strategies for difficult financial situations undertaken by poor families benefiting from social assistance vary depending on the type of family, problem(s) they experience and the resources they have. The strategies undertaken also depend on the gender of family members experiencing poverty. Keywords: poverty, family, social assistance, social worker, gender